Therapeutic hypothermia for encephalopathic newborns with congenital heart defect: A cross-sectional survey on current practices and opinions in Germany - Boos, Vinzenz; Berger, Felix (Frontiers in Pediatrics, 2022)
Background: Therapeutic hypothermia (TH) reduces neonatal mortality and long-term neurodevelopmental impairment in infants with moderate-to-severe hypoxic-ischemic encephalopathy (HIE) caused by perinatal asphyxia. There is an increasing trend to apply TH in other indications and populations, such as infants with mild HIE or neonates with congenital heart defects (CHD), even though there is little evidence to support or refute this. Objective: The aim of this survey was to analyze practice variations with respect to TH use in neonates with CHD and to assess expert opinions on this topic across tertiary neonatal departments in Germany. Methods/Design: A web-based survey was sent to all tertiary neonatal departments in Germany. The questionnaire contained 32 multiple-choice questions. The survey inquired current practices on TH in newborns with CHD and expert opinions on various clinical scenarios. Main results: 80 (51.3%) neonatal departments partially completed the survey, and 69 (44.2%) respondents filled out the whole questionnaire. All 80 (100.0%) departments perform TH. TH is offered by 76 (95.0%) respondents to encephalopathic newborns with simple CHD. In infants with critical/complex CHD, TH is offered after perinatal asphyxial HIE and in newborns with encephalopathy after severe acidosis associated with cardiac complications by 25 (31.3%), or 17 (22.1%) respondents, respectively, whereas a clear majority of centers reject TH in these infants. Unclear effects of TH on any ongoing prostaglandin therapy (57.6% and 52.3%, respectively), an increased risk for adverse reactions during TH (51.6% and 52.3%, respectively) and lack of evidence (33.3% and 53.8%, respectively) are the most frequently cited reasons for not performing TH in these infants. The majority of experts from neonatal departments providing comprehensive care for neonates with severe CHD support the initiation of TH in encephalopathic neonates. Discussion: The considerable heterogeneity in the use of TH in neonates with CHD emphasizes the need for further research to optimize treatment strategies for these patients.